INCREASING LITERACY IN THE COMMUNITY THROUGH COMMUNITY READING PARK (TBM) ACTIVITIES IN WANO VILLAGE - Roni, Roni Romansah; Didin, Didin Junaedi; Ridhawa, Ridhawa Kusumah; Bilal, Bilal Alriziq; Karom, Didi Muhtarom; Dita, Dita Nurjanah; Firda, Firda Rahmawati; Tiara, Tiara Rahma Puspita (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM Azramedia Indonesia, 2024)
Community interest in reading in Wano Village is still relatively low, this is known through observations, namely the unavailability of reading source facilities so as to cause low community interest in reading in Wano Village and the unavailability of adequate facilities and infrastructure for libraries in education units in Wano Village so that it creates problems regarding the lack of literacy. Community service program activities are carried out regularly which are attended by the surrounding community, especially children. The purpose of this service is to increase knowledge, build togetherness and solidarity between residents. The research method used in this research is qualitative research using descriptive methods. Data collection techniques by conducting observations, interviews, and documentation. The results of this study are causing a lot of positive responses from the community, an increase in reading interest, and the active involvement of KKN students of Muhammadiyah Kuningan University.